The Ethics of Digital Communication and Message Sharing on Social Media - Anshar, Muhammad; Arsal, Andi Faridah (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2023)
The present research examines the ethical concerns of social media users in sharing information and digital interaction. Adopting a phenomenological approach, 20 students from two state universities in Makassar South Sulawesi were invited to an interview regarding the issues. The findings illustrate four important ethics concerning digital communication and sharing information on social media: first social media users should convey messages honestly; second, they must be responsible in their words and deeds; third, they have to be polite to others; fourth they have to be tolerant of differences. In addition, this study argues that social media content creators and users respect ethnic, religious, racial, and inter-group diversity in sharing information.